Características, fatores críticos e indicadores de agilidade no gerenciamento de projetos de produtos inovadores - Almeida, Luís Fernando Magnanini de (Universidade Federal de São Carlos, 2012)
The theory of project management presents difficulties when applied to the development of innovative products. To solve these difficulties, a series of management methods were created. These methods receive the nomenclature of agile project management and increase the agility of the management process which would be a strategy to deal with the difficulties in those particular projects. However, the concept of agility is vague in the project management theory and the studies found that attempts to measure this performance was not satisfactory, presenting too much subjectivity in the definitions of constructs and starting from little robust definitions of agility. To try to solve this problem, a new model for agility in project management was proposed by Conforto (2011), relying on a definition coined from a systematic literature review of several areas that exhibit this same concept, and perform another systematic review on the models to measure agility in order to incorporate their strengths and create solutions to major weaknesses. This study aims to examine the relationships between the dimensions present in this model of agility to manage projects, in order to verify its validity and possibility its future use as a basis for measurement. Thus, the observed relationships between some features arising from the use of practices from the theory of agile project management theory, critical factors that may impact on the performance of the practices and indicators of agility. For this, a survey was made at the members from eight communities in Brazil Linkedin® chosen from among 79 candidates and selected according to 7 criteria. Also, was created the theoretical concept of "profile 500" which can be used in future research with have analysis made between members of this social network. There was obtained 172 valid responses from 966 users considered eligible for the study. Correlation analysis showed that the relationships proposed in the model of Conforto (2011) are valid and that agility is related to the presence of certain characteristics and are not inherent to the management method chosen, but this performance is related to customer participation and time taken decision. Finally, there was evidenced the importance of customer participation in the design and validation of partial results for a faster management process, and the necessity of carrying out the planning, development and validation with the participation of the client to perform better agility.
Keywords: Engenharia de produção; Gestão de projetos; Desenvolvimento de produtos; Medição de desempenho; Modelo de agilidade; Gerenciamento agil de projetos; Agilidade; Agile project management; Product development; Project management; Agility model; Agility; ENGENHARIAS::ENGENHARIA DE PRODUCAO